Mocking enactments: a case study of multimodal stance-stacking - de Vries, Clarissa; Andries, Fien; Meissl, Katharina (Frontiers in Psychology, 2024)
Although research into multimodal stance-taking has gained momentum over the past years, the multimodal construction of so called stacked stances, has not yet received systematic attention in the literature. Mocking enactments are a prime example of such complex social actions as they are layered both interactionally and stance-related, and they rely significantly on the use of bodily-visual resources, depicting rather than describing events and stances. Using Du Bois' (2007) Stance Triangle as a framework, this study investigates mocking enactments as a case study to unravel the multimodal aspects of layered stance expressions. Drawing on three data sets-music instruction in Dutch, German and English, spontaneous face-to-face interactions among friends in Dutch, and narrations on past events in Flemish Sign Language (VGT)-this study provides a qualitative exploration of mocking enactments across different communicative settings, languages, and modalities. The paper achieves three main objectives: 1) Illuminating how enactments are used for mocking, 2) Identifying the layers of stance-taking at play, and 3) Examining the multimodal construction of mocking enactments. Our analysis reveals various different uses of enactments for mocking. Aside from enacting the target of the mockery, participants can include other characters and viewpoints, highlighting the breadth of the phenomenon under scrutiny. Secondly, we uncover the layered construction of stance on all axes of the Stance Triangle (evaluations, positioning and alignment). Thirdly, we find that mocking enactments are embedded in highly evaluative contexts, indexed by the use of bodily-visual resources. Interestingly, not all mocking enactments include a multimodally exaggerated depiction, but instead, some merely allude to an absurd hypothetical scenario. Our findings contribute to the growing body of literature on multimodal stance-taking, by showing how a nuanced interpretation of the Stance Triangle can offer a useful framework for analyzing layered stance-acts.